PENGARUH KETERAMPILAN GURU MEMBUKA PELAJARAN TERHADAP MOTIVASI BELAJAR SISWA - Rizka Ramadhaningsih; Fitriah; Nor Amalia Abdiah (Lubna : Journal of Islamic Elementary Education, 2024)
Learning activities are the primary means of achieving a learning goal in the classroom. In the learning process in the classroom, a professional teacher must master basic skills in teaching, especially skills in opening lessons. A teacher's ability to open lessons effectively will impact an effective learning process, motivating him to learn in class. The purpose of this study was to determine: 1). The level of teacher opening skills at MIN 9 Hulu Sungai Tengah; 2). The effect of teacher opening skills on student learning motivation at MIN 9 Hulu Sungai Tengah. This is a quantitative study, and the population of this study is all students at MIN 9 Hulu Sungai Tengah, a total of 183, with a sample of up to 26 students in class VI. The main method used is the questionnaire, while the supporting methods are observation and documentation. The results showed that the teacher's skill level in opening lessons was in the high category, with the largest presentation score of 57.7%. Meanwhile, the impact of the teacher's opening lesson skills on student learning motivation is significant. This can be shown by the t-count value of 28.718 and the t-table of 2.060, which have a sig level of 0.0000168, which means it is less than 0.05 or 5%. If sig 0.05, H0 is rejected and Ha is accepted, according to the test criteria. So, it can be concluded that the independent variable has a significant effect on the dependent variable, and the hypothesis is accepted, meaning that the teacher's skill in opening lessons affects learning motivation.